2020
DOI: 10.1101/2020.05.29.123810
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dose-dependent response to infection with SARS-CoV-2 in the ferret model: evidence of protection to re-challenge

Abstract: 41In December 2019 an outbreak of coronavirus disease emerged in 42 Wuhan, China. The causative agent was subsequently identified and named severe 43 acute respiratory syndrome coronavirus 2 (SARS-CoV-2) which rapidly spread 44 worldwide causing a pandemic. Currently there are no licensed vaccines or 45 therapeutics available against SARS-CoV-2 but numerous candidate vaccines are in 46 development and repurposed drugs are being tested in the clinic. There is a vital need 47 for authentic COVID-19 animal model… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
113
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(137 citation statements)
references
References 36 publications
24
113
0
Order By: Relevance
“…In our study, all hamsters tended to gain weight overtime although at different rates, in spite of local evidence of infection. Inoculated ferrets generally present even milder clinical signs of disease, independently from the challenge dose (8)(9)(10)(11), without any weight loss, as reported in our study. The marked lethargy observed in ferrets in this study was also reported by others (8)(9)(10)(11).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…In our study, all hamsters tended to gain weight overtime although at different rates, in spite of local evidence of infection. Inoculated ferrets generally present even milder clinical signs of disease, independently from the challenge dose (8)(9)(10)(11), without any weight loss, as reported in our study. The marked lethargy observed in ferrets in this study was also reported by others (8)(9)(10)(11).…”
Section: Discussionsupporting
confidence: 84%
“…Antibody kinetics in ferrets and hamsters were comparable with 1/ those seen in patients with a seroconversion between D7 and D14 (22), and 2/ those seen in experimental models using hamsters and ferrets (6,(8)(9)(10)(11). In our study, the increase in antibody levels occurred faster in hamsters than in ferrets, from no detectable level at D4 to consistently high levels between D7 and D14 in hamsters and between D7 and D10 in ferrets.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations